Use-dependent directional bias does not transfer to the untrained limb during bimanual contractions - Marinovic, Welber; Homan, M.; Carroll, T. (2017)
Skills learned through practice with one limb can often be transferred to the untrained limb. In the present report, we sought to determine whether movement direction biases, acquired through repeated movement with one limb, transfer to the untrained limb. In order to do so, we asked participants to perform synchronized bilateral contractions of muscles in both wrists, followed by the unilateral contraction of muscles in one wrist. In four experiments, we manipulated the position of the unilateral target to create use-dependent directional biases; changed the direction of the cursor in relation to the wrist movement to control for attentional biases; and sought to induce directional biases with both right and left unilateral movements. The results showed clear movement-related biases for the wrist that performed unilateral contractions, but no evidence that movement-related bias transferred to the opposite limb during bilateral action. Thus, motor preparation and execution of unilateral contractions does not affect the direction of movement made by the opposite limb during subsequent bilateral contractions.